Autologous oocyte cryopreservation in women aged 40 and older using minimal stimulation IVF. Issue 1 (December 2015) - Zhang, John; Choo, Simon; Yang, Mingxue
Abstract Background The value of oocyte cryopreservation in older women remains controversial. The aim of this study was to report the oocyte freezing experience in women aged 40 and older at a single fertility center. Findings One hundred fifty eight women (mean age 43.9 ± 0.2) who underwent minimal ovarian stimulation IVF were enrolled. IVF protocol included the use of clomiphene citrate (50 mg/day) or letrozole (2.5 mg/day) with or without low dose gonadotropins (started at 75 IU/day and increased as needed to 150 IU/day). 584 retrieved oocytes (2.1 ± 0.15 per patient) yielded 532 mature MII oocytes that were frozen. After thawing and fertilization by ICSI, a total of 344 embryos (1.9 ± 0.1 per patient) were formed. A total of 57 relatively good embryos were transferred and yielded three live births (5.3 % per embryo transfer), three spontaneous abortions, and one chemical pregnancy. Conclusions These data are important in counseling older women who desire autologous oocyte freezing.